Uji Fisik Formulasi Hand Sanitizer Dengan Bahan Aktif Daun Sirih (Piper betle L) Dari Desa Luhu Kecamatan Huamual Kabupaten Seram Bagian Barat - Alice M CL Luhulima; Aulia Debby Pelu; Jahra Palembang (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
The rise of disease outbreaks caused by microorganisms such as SARS, bird flu, HIV and COVID-19 has made people use products that contain antiseptics such as soap and hand sanitizer. However, if used continuously it will dissolve the layer of fat and sebum on the skin so that the skin becomes sensitive, dry, and irritated. The development of antiseptic products can be done with natural ingredients such as green betel leaf extract (Piper betle L). It is known that green betel leaf (Piper betle L) has long been used in traditional medicine and can be a natural antiseptic ingredient for making hand sanitizer. This study aims to determine the formulation of hand sanitizer from betel leaf extract (Piper betle L) accompanied by a physical stability test. The materials used in this study were methyl paraben, triethanolamine (TEA), glycerin, aquadest, 95% ethanol, lime juice, green betel leaf extract obtained from the reflux extraction process. The research was conducted by varying the betel leaf extract 55%, 60%, 65%, 70%, 75%. Tests were carried out by covering organoleptic observations (shape, color, odor), pH, homogeneity, dispersion.